MODEL PENGEMBANGAN KELEMBAGAAN AGRIBISNIS UNTUK MEMBERDAYAKAN PETANI MISKIN BERBASIS MODAL SOSIAL - Rozikin, Zainur (Jurnal Teknologi dan Manajemen Informatika, 2015)
Process reorder point of purchase supplementary materials in the production of cigarettes is one of the main processes in the production chain smoking. Inaccuracy decision will impact the delay in the production process and the cost of storage in the warehouse . Semi-manual system used so far to deal with the reorder point is no longer able to accommodate the increasing number of orders and product variations . Design of decision support systems that integrate multiple parts associated with the reorder point can accommodate inaccuracies reorder point during this proces.Â DOI: https://doi.org/10.26905/jtmi.v1i1.609